2008
DOI: 10.1093/cercor/bhm246
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Correlates of True and False Recognition

Abstract: The Deese/Roediger–McDermott (DRM) false-memory effect has been extensively documented in psychological research. People falsely recognize critical lures or nonstudied items that are semantically associated with studied items. Behavioral research has provided evidence for age-related increases in the DRM false-recognition effect. The present event-related functional magnetic resonance imaging study was aimed at investigating neurodevelopmental changes in brain regions associated with true- and false-memory rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
100
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 63 publications
(110 reference statements)
9
100
1
1
Order By: Relevance
“…Continued development of the hippocampus in middle childhood and adolescence also influences encoding and retrieval [66][67] . Indeed, a recent fMRI study examining activation of brain regions during memory retrieval in 8-and 12-year-olds and adults found that age-related increases in semantic memory errors were related to changes in the pattern of engagement of the left anterior MTL, left posterior parietal cortex, and the left ventrolateral prefrontal cortex (vlPFC) 70 .…”
Section: Findings From Neurobiological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Continued development of the hippocampus in middle childhood and adolescence also influences encoding and retrieval [66][67] . Indeed, a recent fMRI study examining activation of brain regions during memory retrieval in 8-and 12-year-olds and adults found that age-related increases in semantic memory errors were related to changes in the pattern of engagement of the left anterior MTL, left posterior parietal cortex, and the left ventrolateral prefrontal cortex (vlPFC) 70 .…”
Section: Findings From Neurobiological Studiesmentioning
confidence: 99%
“…In terms of retrieval, increased cognitive control lets children selectively remember and rehearse relevant information and selectively suppress or omit irrelevant information. For example, when examining retrieval of memories in children (8-to 12-year-olds) and adults, differences in activation patterns in several PFC areas (left dlPFC, rostrolateral PFC, and vlPFC) were related to age 70 , suggesting developmental improvements in discriminating relevant from irrelevant information in memory and better, more flexible use of semantic retrieval cues 74 .…”
Section: Findings From Neurobiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been suggested that frontal and associative areas of the brain (prefrontal and lateral temporal areas) are the last to mature, resulting in the late development of higher-order executive and associative functions (see Craik, 2006, for a review). Specifically for memory and false memory development, it has been found that immaturities in the medial temporal lobe and the prefrontal cortex (left ventrolateral area) can explain age-related differences in false memories (Paz-Alonso, Ghetti, Donohue, Goodman, & Bunge, 2008). In contrast, knowledge and memory representations develop from birth and mature gradually during childhood.…”
Section: False Recognition Of Critical Lures and Strongest Associatesmentioning
confidence: 99%
“…Conversely, data from Østby et al (2011) and DeMaster, Pathman, Lee, and Ghetti (2012) suggest that increases in the reliability of consolidation processes may be related to changes in hippocampal volume (see also Lee, 2014 andSowell, Delis, Stiles, &Jerningan, 2001, for discussion). Regionspecific activation in the hippocampus-specifically, in the anterior region-has been linked with better memory for the types of associations among stimuli that are part-and-parcel of episodic memory (Paz-Alonso, Ghetti, Donohue, Goodman, & Bunge, 2008;Ghetti, DeMaster, Yonelinas, & Bunge, 2010).…”
mentioning
confidence: 99%